Utilization of Nutgrass (Cyperus Rotundus L.) as a Phytoremediator in Reducing BOD and COD Levels of Batik Liquid Waste Using Constructed Wetlands in Sub-Surface Flow Type - Irsyada, Muhamad Zakky; Fauziyyah, Hasna Amalia; Sari, Ayuk Permata (Universitas Negeri Semarang, 2023)
The process of dyeing batik fabric is a significant source of water pollution due to synthetic dyes. Only 5% of this compound is used, while 95% will be disposed of as waste. This compound is relatively stable, so it is tough to degrade in nature and is dangerous for the environment because it can cause effects such as increasing COD (Chemical Oxygen Demand) and BOD (Biological Oxygen Demand). Constructed wetlands in sub-surface flow type is a wastewater treatment method that utilizes the role of plants and microorganisms found in the plant root area or rhizosphere. Nutgrass (Cyperus Rotundus L.) is rarely used and is considered a weed that causes harm to surrounding plants. On the other hand, nutgrass is a plant with good remediation and straightforward maintenance. In this research, the nutgrass plant was used as a phytoremediator with planting media in the form of sand and gravel to improve the performance of constructed wetlands in processing liquid batik waste. Based on the analysis of BOD and COD test parameters, the results showed that nutgrass could reduce BOD levels by up to 75% and COD levels by 73% so that wastewater produced from artificial wetlands flows more safely and can be used for irrigation and plants sanitation.